A novel LightGBM-LSTM-GA framework for performance degradation prediction of composite laminates with variable structural parameters - Xin He; Datong Liu; Huizhen Hua; Hua Zhang; Yafei Xu (Engineering Structures, 2026)

Seasonal source shifts and toxicity implications of PM2.5-bound polycyclic aromatic hydrocarbons in central China: The critical role of underrated local emissions - Runqi Zhang; Sheng Li; Qiongwei Zhang; Jun Wang; Datong Luo; Zhan Liu; Xinming Wang (Atmospheric Pollution Research, 2026)

Development and characterization of a novel compensating wheat–Dasypyrum villosum interstitial translocation line Dv6-IT1 carrying the powdery mildew resistance gene PmV - Renhui Zhao; Wentao Wan; Man Xu; Tiantian Chen; Ling Wang; Ronglin Wu; Shujiang Zang; Zunjie Wang; Wei Jiang; Datong Liu; Yong Zhang; Xiue Wang; et al. (Theoretical and Applied Genetics, 2026)

Field observations reveal biomass burning and cooking as the significant sources of PM2.5-bound organic acids in Central China - Ziyue Xiang; Runqi Zhang; Sheng Li; Bin Xu; Qiongwei Zhang; Jun Wang; Datong Luo; Zhan Liu; Xinming Wang (Atmospheric Environment, 2026)

Telomere-to-telomere genome assembly reveals the genomic architecture of disease resistance and yield coordination in elite wheat YM33 - Guofeng Lv; Yating Wang; Heping Zhang; Yuning Shen; Wenjing Hu; Datong Liu; Mengmeng Liu; Wenna Wang; Yuwen Gao; Caixia Lan; Tongde Bie; Hongya Wu; et al. (Molecular Plant, 2026)

Hazardous mode and vibration source identification based on the rigid-flexible coupled model: An application on AUVs powertrain - Dingchang He; Yonggang Liu; Jing Wei; Datong Qin; Yi Zhang (Ocean Engineering, 2025)

DDM1 Controls Heritable Natural Epigenetic Variation in Arabidopsis - Peng Zhang; Datong Xing; Muhammad Shahbaz Chishti; Linan Xie; Qingzhu Zhang (Molecular Ecology, 2025)
As a part of epigenetic modifications, DNA methylation involves the addition of a methyl group to cytosine. In plants, this process occurs in three sequence contexts (CG, CHG and CHH) through two pathways: de novo DNA methylation and DNA methylation maintenance. DNA methylation is highly conserved between ecotypes due to its heritability and role in genomic stability. However, numerous naturally occurring differentially methylated regions (NMRs) exist between ecotypes, which are also heritable and contribute to differential gene expression and phenotypic variation. Decreased DNA methylation observed in mutants of RdDM or DNA methylation maintenance pathways highlights the potential roles of these pathways in NMR formation and inheritance. Nevertheless, the complexity of plant DNA methylation across different contexts and pathways has made the contributions of these two pathways in NMR formation and inheritance remain unclear. To address this, we chose two Arabidopsis thaliana ecotypes, Col‐0 (Col) and C24, and utilised mutants of pol4/5 and ddm1 in both ecotypes. By examining the changes in NMRs within these mutants, we aimed to elucidate the roles of DNA methylation pathways in NMR formation and inheritance. Our results revealed (1) NMRs can be categorised into three types, but classification is not solely based on methylation contexts; (2) compared to RdDM, the DNA methylation maintenance pathway plays a more dominant role in NMR formation and is less influenced by SNPs; (3) DNA methylation maintenance, rather than RdDM, controls NMR inheritance. Our findings highlight the role of the DNA methylation maintenance pathway in NMR formation and inheritance.

Optimizing N applications increases maize yield and reduces environmental costs in a 12-year wheat-maize system - Shuaijie Shen; Biao Feng; Datong Zhang; Jun Zou; Yuhao Yang; Robert M. Rees; Cairistiona F.E. Topp; Suya Hu; Bowen Qiao; Wenhai Huang; Hongbao Sun; Shiwei Zhou; et al. (Field Crops Research, 2025)

Optimizing N rate in wheat-maize rotation to match long-term and inter-seasonal N turnover for high yield and sustainability using STICS - Datong Zhang; Shuaijie Shen; Zhiyuan Bai; Matthew Tom Harrison; Ke Liu; Robert M. Rees; Cairistiona F.E. Topp; Jun Zou; Yuhao Yang; Zhenwei Song; Haotian Chen; Xiaogang Yin (Field Crops Research, 2025)

Optimal sowing time to adapt soybean production to global warming with different cultivars in the Huanghuaihai Farming Region of China - Haoyu Zheng; Li Zhang; Hongbao Sun; Axiang Zheng; Matthew Tom Harrison; Wenjie Li; Jun Zou; Datong Zhang; Fu Chen; Xiaogang Yin (Field Crops Research, 2024)

Intermediate-volatility aromatic hydrocarbons from the rubber products industry in China - Zhou Zhang; Yanli Zhang; Lilin Zou; Zhongxiangyu Ou; Datong Luo; Zhan Liu; Zhonghui Huang; Leilei Fei; Xinming Wang (Science of The Total Environment, 2023)

Compensatory thalamocortical functional hyperconnectivity in type 2 Diabetes Mellitus - Jie Wang; Shanlei Zhou; Datong Deng; Mimi Chen; Huanhuan Cai; Cun Zhang; Fujun Liu; Wei Luo; Jiajia Zhu; Yongqiang Yu (Brain Imaging and Behavior, 2022)

Association of CDKN1B gene polymorphisms with susceptibility to breast cancer: a meta-analysis - Heping Xiang; He Li; Weiwei Ge; Weidong Wu; Ming Gao; Wei Wang; Lei Hong; Datong Jiang; Changle Zhang (Molecular Biology Reports, 2013)

Synthesis and preliminary antibacterial evaluation of hydroxamic acid and N-formyl hydroxylamine derivatives bearing oxazole ring - Datong Zhang; Lingyan Huo; Laichun Lu; Qiong Yu; Jianwu Wang; Yanyan Yang (Medicinal Chemistry Research, 2013)

Molecular Phylogeny of the Genus Paramesotriton (Caudata: Salamandridae) - Shunqing Lu; Zhi-Gang Yuan; Junfeng Pang; Datong Yang; Fahong Yu; Peter McGuire; Feng Xie; Ya-Ping Zhang (Biochemical Genetics, 2004)